ATP synthase in rat brain neurons - Uzlova, Elizaveta V.; Zimatkin, Siarhei M. (Experimental Biology and Biotechnology, 2021)
Mitochondrial ATP synthase is the main enzyme of ATP synthesis. A large number of diseases, including neurodegenerative ones, are associated with disorders of its assembly and functioning. The aim of the work is to reveal the patterns and features of the regional distribution of ATP synthase in the neurons of the rat brain structures, with a quantitative assessment of its content at the cellular level. The study was carried out on material from 5 outbred white male rats. Paraffin sections were stained by the Nissl method to identify structures of the brain and cervical segments of the spinal cord, and for ATP synthase by immunohistochemical method; 102 structures of the rat brain were studied cytophotometrically. Immunoreactivity of ATP synthase was found in all structures of the rat brain with high heterogeneity, while most structures are characterised with a moderate content of ATP synthase. A high content of ATP synthase was found in large neurons and in neurons of structures of phylogenetically older brain divisions. The content of ATP synthase also depends on the layer of the cortex and the position of neurons in the reflex arc. In the spinal cord the content of ATP synthase depends not only on the size of neurons, but also on the gray matter layer.